2011
DOI: 10.1007/s00170-011-3725-4
|View full text |Cite
|
Sign up to set email alerts
|

Simulated annealing algorithm for balanced allocation problem

Abstract: This paper deals with the balanced allocation of customers to multiple third party logistics warehouses. The allocation problem generally deals with clustering of customers so as to achieve minimum total resource viz. cost or time. But the real challenge arises when it is required to strike a balance between the allocation while also minimizing the total cost or time. Since the problem develops to be non-deterministic polynomial-time hard, the paper uses simulated annealing approach to solve the problem. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For the inequality metric, Rajesh et al. (2012) used SA to solve the same allocation problem of Zhao et al. (2011), which is described in the previous paragraph.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For the inequality metric, Rajesh et al. (2012) used SA to solve the same allocation problem of Zhao et al. (2011), which is described in the previous paragraph.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed that SA notably outperformed the interchange heuristic for all considered problems. For the inequality metric, Rajesh et al (2012) used SA to solve the same allocation problem of Zhao et al (2011), which is described in the previous paragraph. The authors further compared allocations resulting from their SA-based technique to those resulting from the GA-based approach of the latter article.…”
Section: Single-objective Ga-and Sa-based Allocation Of Facilitiesmentioning
confidence: 99%
“…Reference [33] presented a memetic algorithm for a multistage supply chain problem. Reference [34] proposes a simulated annealing algorithm for an allocation problem. Reference [35] presents a hybrid approach using an artificial bee algorithm (BA) with mixed integer programming (MIP) applied to a large-scale CFLP; BA is applied for the purpose of solving the location problem, and the MIP is applied for the purpose of finding the optimal mathematical problem.…”
Section: Literature Reviewmentioning
confidence: 99%